What is the best clinical approach to recurrent/refractory osteosarcoma?. Issue 5 (3rd May 2020) - Meazza, Cristina; Bastoni, Stefano; Scanagatta, Paolo
ABSTRACT: Introduction : Osteosarcoma is the most common malignant bone tumor. It is currently treated with pre-and postoperative chemotherapy, associated with surgical resection of the tumor. Area covered : Relapses occur in about one in three patients presenting with localized disease, and three in four of those with metastases at diagnosis. Relapsing disease carries a very poor prognosis, with 5-year survival rates ranging between 13% and 40%. Expert opinion : Patients with unilateral lung involvement or solitary lung metastases and a recurrence-free interval (RFI) longer than 24 months have a better prognosis, and could be managed with surgical resection and close observation. Complete surgical resection of all sites of disease remains essential to survival: patients unable to achieve complete remission have a catastrophic overall survival rate. The role of second-line chemotherapy is not at all clear, and no controlled studies are available on this topic. It is worth considering for patients unable to achieve complete surgical remission, and those with multiple metastases and/or a RFI <24 months. Given their dismal prognosis, patients with multiple sites of disease not amenable to complete surgical resection should also be considered for innovative therapeutic approaches.